PENGARUH KOMPETENSI DAN REKRUTMEN TERHADAP KINERJA DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASI: (Studi Kasus Pada Kantor Desa Jayamukti Kecamatan Cikarang Pusat) - Ari Mulyono Hadi; Julius Ristiano Rifaldy; Andi Mulyadi; Agil Sahrial Putra; Adi Fazryan; Surya Bintarti (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
Village officials are one of the elements of the perpetrator villages that have an important role and become a supporting factor in efforts improving the performance of a government agency. The village apparatus consists of from the village secretary and other village officials who are village officials under the auspices of the village head. This study was conducted aimed at measuring and testing how much influence apparatus and recruitment competence has on the performance of the Jayamukti village government apparatus with organizational culture as moderation variables. This research was conducted within the scope of the village government at the Jaya Village Office mukti, Cikarang Central District, Bekasi Regency. Population in this study is the village apparatus at the Jayamukti village office which is probability or already known and done by method Quantitative. The number of samples contained in the Jayamukti Village Office There were 34 respondents, with data collection carried out using questionnaire. This research shows that competence and recruitment are capable Encouraging the improvement of the quality of performance of the village apparatus, while culture organization as a modulator of the relationship of competence to performance shows that moderation variables cannot drive improved performance quality Jayamukti village apparatus